2016
DOI: 10.2174/1874440001610010111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Neurocircuitry Underpinning Predictability of Threat in Soldiers with PTSD Compared to Deployment Exposed Controls

Abstract: Background:Prior work examining emotional dysregulation observed in posttraumatic stress disorder (PTSD) has primarily been limited to fear-learning processes specific to anticipation, habituation, and extinction of threat. In contrast, the response to threat itself has not been systematically evaluated.Objective:To explore potential disruption in fear conditioning neurocircuitry in service members with PTSD, specifically in response to predictable versus unpredictable threats.Method:In the current study, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 63 publications
2
22
1
Order By: Relevance
“…This is in line with previous studies showing increased difficulties returning to initial emotional states after negative emotions in participants with anxiety symptoms [ 18 ] and the result of higher anxiety symptoms in patients with PTSD [ 64 , 65 ]. Physiological stress responses did not differ between the groups, which is in contrast to our expectation and a previous fMRI study showing increased skin conductance responses to unpredictable threat in individuals who were exposed to stressful events and in patients with PTSD [ 66 ]. Our finding that there is no difference in physiological stress responses between HA and LA may be related to (i) a blunted hormonal and skin conductance response to acute stress found to be specific for HA individuals [ 67 , 68 ], (ii) efficient coping behaviour [ 69 ] or (iii) the fact that analogue traumatic situations are less intense than real traumatic situations [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with previous studies showing increased difficulties returning to initial emotional states after negative emotions in participants with anxiety symptoms [ 18 ] and the result of higher anxiety symptoms in patients with PTSD [ 64 , 65 ]. Physiological stress responses did not differ between the groups, which is in contrast to our expectation and a previous fMRI study showing increased skin conductance responses to unpredictable threat in individuals who were exposed to stressful events and in patients with PTSD [ 66 ]. Our finding that there is no difference in physiological stress responses between HA and LA may be related to (i) a blunted hormonal and skin conductance response to acute stress found to be specific for HA individuals [ 67 , 68 ], (ii) efficient coping behaviour [ 69 ] or (iii) the fact that analogue traumatic situations are less intense than real traumatic situations [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Items are rated using a 5‐point Likert scale; 1 = “Not at all” through 5 = “Extremely.” A total symptom severity score (range: 20–100) is obtained by summing the scores for each of the 20 items, with a cut score of 38 for a precursory diagnosis of PTSD [Weathers et al, ]. PCL5 has been shown to be able to differentiate between soldiers with PTSD and healthy controls [Dretsch et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas Lis et al (2019) concluded a crucial role for compromised expectation with subsequent overgeneralization of threat and undergeneralization of safety signals from fear-potentiated startle and subjective measures, other articles used structural and functional brain imaging to identify predictors of PTSD susceptibility. Resting-state network connectivity and activity in response to fear or trauma-related stimuli in the hippocampus, amygdala, insula, and prefrontal cortex have been found to predict PTSD in trauma-exposed individuals (e.g., see overviews by Suarez-Jimenez et al, 2019;Dretsch et al, 2016). In the present volume, Sambuco et al (2019) suggest that post-traumatic stress, related affective psychopathology, and trauma exposure, when considered transdiagnostically, may confer a risk for emotional hyporeactivity: fMRI was monitored while patients with different anxiety and mood disorders viewed emotional and neutral scenes.…”
mentioning
confidence: 99%